Lymph node metastasis diagnosis of postoperative OSCC patients by analyzing extracellular vesicles in drainage fluid based on microfluidic isolation - Zi-Zhan Li; Ze-Min Cai; Wen-Tao Zhu; Nian-Nian Zhong; Lei-Ming Cao; Guang-Rui Wang; Yao Xiao; Zhao-Qi Zhu; Xuan-Hao Liu; Ke Wu; Rong-Xiang He; Xing-Zhong Zhao; et al. (Journal of Nanobiotechnology, 2024)
Abstract Lymph node metastasis (LNM) is a typical marker in oral squamous cell carcinoma (OSCC) indicating poor prognosis. Pathological examination by artificial image acquisition and analysis, as the main diagnostic method for LNM, often takes a week or longer which may cause great anxiety of the patient and also retard timely treatment. However, there are few efficient fast LNM diagnosis methods in clinical applications currently. Our previous study profiled the proteomics of extracellular vesicles (EVs) derived from postoperative drainage fluid (PDF) and showed the potential of detecting specific EVs that expressed aspartate β-hydroxylase (ASPH) for LNM diagnosis in OSCC patients. Considering that the analysis of ASPH+ PDF-EVs is challenging due to their low abundance (counting less than 10% of total EVs in PDF) and the complex EV isolation process of ultra-centrifugation, we developed a facile platform containing two microfluidic chips filled with antibody-modified microbeads to isolate ASPH+ PDF-EVs, with both the capture and retrieval rate reaching around 90%. Clinical sample analysis based on our method revealed that a mean of 6 × 106 /mL ASPH+ PDF-EVs could be isolated from LNM+ OSCC patients compared to 2.5 × 106 /mL in LNM- OSCC ones. When combined with enzyme-linked immunosorbent assay (ELISA) technique that was commonly used in clinical laboratories in hospitals, this microfluidic platform could precisely distinguish postoperative OSCC patients with LNM or not in several hours, which were validated by a double-blind test containing 6 OSCC patients. We believe this strategy has promise for early diagnosis of LNM in postoperative OSCC patients and finally helps guiding timely and reasonable treatment in clinic.